Corrosion fatigue of biomedical metallic alloys: Mechanisms and mitigation - Antunes, Renato Altobelli; de Oliveira, Mara Cristina Lopes (Acta biomaterialia, 2012)
Cyclic stresses are often related to the premature mechanical failure of metallic biomaterials. The complex interaction between fatigue and corrosion in the physiological environment has been subject of many investigations. In this context, microstructure, heat treatments, plastic deformation, surface finishing and coatings have decisive influence on the mechanisms of fatigue crack nucleation and growth. Furthermore, wear is frequently present and contributes to the process. However, despite all the effort at elucidating the mechanisms that govern corrosion fatigue of biomedical alloys, failures continue to occur. This work reviews the literature on corrosion-fatigue-related phenomena of Ti alloys, surgical stainless steels, Co–Cr–Mo and Mg alloys. The aim was to discuss the correlation between structural and surface aspects of these materials and the onset of fatigue in the highly saline environment of the human body. By understanding such correlation, mitigation of corrosion fatigue failure may be achieved in a reliable scientific-based manner. Different mitigation methods are also reviewed and discussed throughout the text. It is intended that the information condensed in this article should be a valuable tool in the development of increasingly successful designs against the corrosion fatigue of metallic implants.